Cover Feature: Acid Activation and Chemical Oxidation in the Synthesis of meso‐Tetraphenylporphyrin using a Mixed‐Solvent System (Asian J. Org. Chem. 4/2019). Issue 4 (2nd April 2019) - Sun, Zhicheng; Jiao, Shouzheng; Li, Furong; Wen, Jinyue; Yu, Yanmin; Liu, Yuanyuan; Cao, Meijuan; Li, Luhai; Zhou, Yang; She, Yuanbin
Abstract : Acidification and oxidation play an important role in the synthesis of meso ‐tetraphenylporphyrin. A mixed‐solvent system of acetic acid, propionic acid, and nitrobenzene derivatives was used to investigate the catalytic role of carboxylic acids, and the oxidation behavior of various nitrotoluene analogs. The acid activation process between benzaldehyde and pyrrole using DFT calculations and the catalytic role were indicated by the formation of a carbocation intermediate. The oxidation behavior and reduction products were confirmed by UV/Vis spectroscopy and HPLC/GC‐MS measurements. More information can be found in the Full Paper by Zhicheng Sun, Yang Zhou, Yuanbin She et al. on page 542 in Issue 4, 2019 (DOI: 10.1002/ajoc.201900154 ).